Application of Astrological Idioms to Twelve Tone Series Technique: Composition “BEYOND 12” - Rafael Dimas Prabowo; Puput Pramuditya; Nugrahanstya Cahya Widyanta (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2026)
This study integrates astrological idioms into musical  composition using the twelve-tone series technique. The  connection between the two is based on the similarity in the  number of variables—namely 12—as well as the principle of  equality. In the twelve-tone series, all 12 notes are treated equally  without any tonal hierarchy, while in astrology, the ecliptic circle is  divided into 12 zodiac signs with equal angles. The creative process  includes idea formulation, title determination, literature review, and  concept development before being realized in a musical  composition. The method used is correlative exploratory and  implementation, linking variables to form the basis of serialist  composition. The creative strategy follows the movement patterns  of the sun and moon in the ecliptic, which is divided into 4  quadrants. These quadrants serve as the foundation for the number  of movements and series transformations. The melody in each  movement is arranged according to zodiac groups, corresponding  to their elements and angles within the geocentric cycle of the sun’s  and moon’s movement.